The Relationship between Social Environments and Smoking Behavior in Adolescents in Taccorong Village, Gantarang District - Nadia Alfira; Muriyati; Irma (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Smoking behavior is influenced by several factors, one of which affects smoking behavior in adolescents is the social environment. The results of a preliminary study stated that many adolescents in Taccorong Village smoked because they were influenced by the number of smokers in the environment around the teenagers. This study aims to determine the relationship of the social environment with smoking behavior in adolescents in Taccorong Village, Gantarang District, Bulukumba Regency in 2017. This study is an analytic study with cross-sectional approach. Sampling is done by total sampling technique. The research sample taken amounted to 52 teenage male smokers in Taccorong Village, Gantarang District, Bulukumba Regency. Measuring instruments used were questionnaires and observations. Analysis of the data used by the Kolmogorov-Smirnov Z test with a value of ρ = 0,000 <α = 0.05 or p <0.001. Shows there is a relationship between the social environment with smoking behavior among adolescents in Taccorong Village, Gantarang District, Bulukumba District.